Decision archetypes in information technology governance: Reflections in small and medium-sized enterprises - Frogeri, Rodrigo Franklin; Pardini, Daniel Jardim; Cardoso, Ana Maria Pereira; Portugal Júnior, Pedro dos Santos (REGEPE Entrepreneurship and Small Business Journal, 2021)
Objective: To understand and analyze the configuration of the decision archetypes proposed by Weill and Ross (2004) in the context of Small and Medium Enterprises (SMEs). The study is justified by the increased organizational dependence on Information and Communication Technologies (ICT) and their high costs, which requires a close alignment between business strategies and the adoption of these technologies. Methodology/Approach: Qualitative approach, under an inductive logic; and data collected through semi-structured, in-depth interviews involving five owner-managers of ICT service providers and 16 directors/managers of Information Technology (IT), in SMEs. Findings: It was observed that SMEs have characteristics that facilitate the integration between business and IT, with the prevalence of the duopoly decision archetype. The greater concentration of power in the owner-manager or the absence of structural power of the key IT professional in these companies can, however, favor federalism or monarchy archetypes, influencing misaligned decisions between IT and business. Theoretical/methodological contributions: The study findings suggest that, in the organizational structures of SMEs, there are key IT professionals with decision-making power, to be backed up by metrics based on quantitative aspects, supported by business intelligence systems and the empirical knowledge of those involved in the process. Relevance/Originality: By proposing mechanisms for configuring decision archetypes in Information Technology Governance (ITG) in SMEs, this study contributes significantly to the advancement of this theme, still incipient in the literature, as well as supporting new research. JEL CODE: M15, M10, G30, L86, D80 <!-- Start Crossmark Snippet v2.0 --> <!-- End Crossmark Snippet -->